Polyphenol Rich Extract of Garcinia pedunculata Fruit Attenuates the Hyperlipidemia Induced by High Fat Diet - Sarma, Rahul; Kumari, Sima; Elancheran, Ramakrishnan; Deori, Meetali; Devi, Rajlakshmi (Frontiers in Pharmacology, 2016)
Fatty foods, the most common diet today are the crux of many metabolic disorders which need urgent attention. Garcinia pedunculata Roxb. (GP, Clusiaceae) is a plant found available in Northeast (NE) region of India, is considered to have versatile therapeutic properties. The people of this region has been using dried pulp of GP fruit for the treatment of different stomach related diseases traditionally. This study aimed at evaluating the potential therapeutic action of the polyphenol-rich methanolic extract (ME) of the fruit in experimental induced obese rats. In vitro antioxidant and antidiabetic activity of GP extracts, i.e., fruit extract (GF) and seed extract (GS) were determined by using various methods viz., 1,1-diphenyl-2 picrylhydrazyl (DPPH), 2,2′-Azinobis (3-ethyl benzthiazoline-6-sulphonic acid) (ABTS•+), nitroblue tetrazolium (NBT) and α-glucosidase inhibition assay for detection of antihyperglycemic activity. In vivo antilipidemic and antiobesity activities were evaluated by administrating oral dose of GF for 60 days on a high-fat diet (HFD) induced hyperlipidemia in the rat. GF showed higher antioxidant activity than GS by DPPH radical scavenging (IC50=4.01 µg/ml), ABTS•+ (IC50=0.82 µg/ml), NBT (IC50=0.07 µg/ml) and also showed notable α-glucosidase inhibitory activity (IC50=19.26 µg/ml). Furthermore, GF treated rat revealed a reduction in the body weight (~60%), serum total cholesterol (33%), triglycerides (32%), low-density lipoprotein (38%) and liver biomarker enzymes after 60 days HFD fed animals. Simultaneously, GF supplementation significantly protected the HFD induced changes in hematological parameters. Histological observations clearly differentiate the structural changes in liver of HFD and GF treated group. This novel dietary lipid adsorbing agent of GF exhibited prevention of hyperlipidemia induced by HFD in the rat.